THE USE OF E-MODULE AS HYPERTEXT-BASED PROCESSING NUMBER IN KKPI SUBJECT TO IMPROVE THE LEARNING RESULTS OF CLASS X.AP.C OF SMK NEGERI 1 SINGARAJA - Ni Made Dwi Puspitayani (Universitas Pendidikan Ganesha, 2012)
This classroom action research was aimed at (1) improving the students’ learning results in KKPI subject of class X.AP.C of SMK Negeri 1 Singaraja through the implementation of e-module as hypertext-based processing number and (2) investigating the students’ responses of class X.AP.C of SMK Negeri 1 Singaraja toward the implementation of e-module as hypertext-based processing number in KKPI subject. This study was a Classroom Action Research which consisted of two cycles. Each cycle consisted of four steps namely planning, action, observation and evaluation, and reflection. The subject of this study was the students of class X.AP.C of SMK Negeri 1 Singaraja in academic year 2011/2012. The class consisted of 40 students. Meanwhile, the objects of this study were (1) students’ learning results and (2) students’ responses toward the implementation of e-module as hypertext-based processing number in KKPI subject. The data of students’ learning results in KKPI subject were collected through the test and observation and the data of students’ responses were collected through questionnaire. The collected data was analyzed by using descriptive analysis. The result of this study showed that the students’ learning results got improvement. In cycle 1, the mean of students’ scores was 74.89 and the percentage of students’ classical success was 70%. In cycle 2, the mean of students’ scores was 78.08 and the percentage of students’ classical success was 85%. Besides, the students’ responses toward the implementation of e-module as hypertext-based processing number in KKPI subject were positive with a mean of 60.05. Key words: e-module as hypertext-based processing number, learning results, Classroom Action Research, and KKPI